Complete genome sequencing and antibiofilm activity of an endophytic bacterium associated with marine sponge Hyrtios erectus collected from the Red Sea - Jamal, Mamdoh T.; Abdulrahman, Idris; Amran, Ramzi H.; Al-Matary, Mohammed A.; Satheesh, Sathianeson (Frontiers in Marine Science, 2025)
Genome sequences of sponge bacterial endophytes will be useful for understanding the bioactive compound synthetic potential and molecular mechanisms of sponge-bacteria interactions. In this study, the complete genome of the bacterium E9 isolated from the Red Sea sponge species was sequenced and its antibiofilm activity was assessed through laboratory assay. Experiments indicated the strong antibacterial and antibiofilm activity of the extracts of bacterium E9. Complete genome sequencing reveals that genome assembly generated a single chromosome of 2123451 base pairs with a guanine-cytosine (GC) content of 32.9% with 2420 protein coding sequences and a gene/genome ratio of 83.7%. The bacterial strain was identified as Staphylococcus epidermidis based on phylogenetic analysis. A total of 9 biosynthetic gene clusters were identified in the genome using the open-source platform AntiSMASH. The observed antibacterial and antibiofilm activity of the strain E9 may be due the presence of gene clusters such as nonribosomal peptides, lasso peptides and terpenes. Overall, the whole genome analysis indicated the bacterium’s capability to adapt in diverse environments including invertebrate hosts, and bioactive compound synthesis.